Sonochemical synthesis, characterization, and magnetic properties of Mn-doped ZnO nanostructures - Nuengruethai Ekthammathat (2018)
© 2017 The Nonferrous Metals Society of China and Springer-Verlag Berlin Heidelberg Mn-doped ZnO samples, Zn1–xMnxO (x = 0, 0.01, 0.03 and 0.05; mole fraction), were successfully synthesized by sonochemical method. The undoped and Mn-doped ZnO samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Raman spectroscopy. XRD patterns of all products are identified to hexagonal wurtzite ZnO structure and their three main peaks shift toward lower diffraction angles due to the incorporation of Mn2+into ZnO crystal lattice. The morphologies of Zn1–xMnxO (x = 0, 0.01, 0.03 and 0.05) were examined by SEM and TEM. The undoped ZnO sample shows large-scale uniform microflowers which are broken into nanorods and nanoparticles by Mn dopant. Their magnetic properties were investigated by a vibrating sample magnetometer at room temperature. The magnetization-applied field behavior of undoped ZnO defines its weak ferromagnetic behavior. The 3 mol% Mn-doped ZnO shows the highest saturation magnetization of 51.73 × 10−3mA·m2·g−1, and the 5 mol% Mn-doped ZnO has suppressed ferromagnetic property due to the formation of Mn clusters inside.